Stroke‐like events after brain radiotherapy: a large series with long‐term follow‐up. (10th January 2019) - Di Stefano, A. L.; Berzero, G.; Ducray, F.; Eoli, M.; Pichiecchio, A.; Farina, L. M.; Cuccarini, V.; Brunelli, M. C.; Diamanti, L.; Condette Auliac, S.; Salmaggi, A.; Silvani, A.; et al.
Abstract : Background and purpose: Patients with a history of brain radiotherapy can experience acute stroke‐like syndromes related to the delayed effects of brain radiation, including stroke‐like migraine attacks after radiation therapy syndrome, peri‐ictal pseudoprogression and acute late‐onset encephalopathy after radiation therapy syndrome. The aim of this study was to collect evidence on the long‐term outcome and treatment of these conditions, whose knowledge is undermined by their rarity and fragmented description. Methods: Cases were collected, both prospectively and retrospectively, amongst six neuro‐oncology departments. Inclusion criteria were as follows: (i) history of brain radiotherapy (completed at least 6 months before the acute episode); (ii) new onset of acute/subacute neurological symptoms; (iii) exclusion of all etiologies unrelated to brain irradiation. A review of current literature on stroke‐like syndromes was performed to corroborate our findings. Results: Thirty‐two patients with acute neurological conditions attributed to the delayed effects of radiation were identified, including 26 patients with stroke‐like syndromes. Patients with stroke‐like syndromes commonly presented with a mosaic of symptoms, including focal deficits (77%), encephalopathy (50%), seizures (35%) and headache (35%). Seventy‐three percent of them had acute consistent magnetic resonance imaging alterations. Treatment included high‐dose steroids in 65% of cases. Twenty‐two patients recovered completely (85%). Sixteen patients (62%) experienced relapses (median follow‐up 3.5 years). A literature review identified 87 additional stroke‐like cases with similar characteristics. Conclusions: Stroke‐like events related to brain irradiation may be associated with permanent sequelae. Steroids are often administered on empirical grounds, as they are thought to accelerate recovery. Relapses are common, highlighting the need to elaborate adequate prevention strategies.